2014
DOI: 10.1161/strokeaha.113.004360
|View full text |Cite
|
Sign up to set email alerts
|

Is the Long-Term Prognosis of Transient Ischemic Attack or Minor Ischemic Stroke Affected by the Occurrence of Nonfocal Symptoms?

Abstract: The present study is a post hoc analysis of the Life Long After Cerebral (LiLAC) ischemia study, which in turn was based on the DTT. The design and results of both studies have been published. 6,7 Background and Purpose-In patients with a transient ischemic attack or ischemic stroke, nonfocal neurological symptoms, such as confusion and nonrotatory dizziness, may be associated with a higher risk of vascular events. We assessed the relationship between nonfocal symptoms and the long-term risk of vascular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(27 reference statements)
1
5
2
Order By: Relevance
“…The higher prevalence of use of oral contraceptives in patients with paresthesia was not reported before. In contrast to previous studies, patients with nonfocal symptoms more frequently had other well-known cardiovascular risk factors [2,4,7] . Significant carotid stenosis was less frequently found in patients with accompanying nonfocal symptoms.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…The higher prevalence of use of oral contraceptives in patients with paresthesia was not reported before. In contrast to previous studies, patients with nonfocal symptoms more frequently had other well-known cardiovascular risk factors [2,4,7] . Significant carotid stenosis was less frequently found in patients with accompanying nonfocal symptoms.…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, in the Rotterdam study, patients were asked to reveal the nonfocal symptoms that they had observed in the last 3 years; conversely in our study, a systematic registration of accompanying nonfocal symptoms was provided shortly after the TIA or minor ischemic stroke. The higher prevalence of nonfocal symptoms in 2 other studies might be due to differently registered nonfocal symptoms and a higher frequency of posterior stroke in these studies [2,3] . In this study, cardiac history was not more frequently observed in patients with accompanying nonfocal symptoms.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations